2022
DOI: 10.3390/ma15041291
|View full text |Cite
|
Sign up to set email alerts
|

On the Effects of Core Microstructure on Energy Absorbing Capabilities of Sandwich Panels Intended for Additive Manufacturing

Abstract: Increasing transportation safety can be observed as one of the biggest engineering challenges. This challenge often needs to be combined with the need to deliver engineering solutions that are able to lower the environmental impact of transportation, by reducing fuel consumption. Consequentially, these topics have attracted considerable research efforts. The present work aims to address the previously cited challenges by maximizing the energy absorption capabilities of hybrid aluminum/composite shock absorbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 18 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…AM is in the center focus, due to its limitless design manufacturability, various customized material deposition, and ability to automate the manufacturing process, which are few key factors that capitalize over traditional manufacturing methods. AM has achieved immense growth, due to progress in several fields, such as numerical simulations, materials modeling, software development related to AM, customized powder materials preparation for AM, characterizing techniques, and so on [ 1 , 2 , 3 , 4 , 5 ]. Virtual engineering, with the help of numerical modeling, is a powerful tool for the swift progress of AM technology.…”
Section: Introductionmentioning
confidence: 99%
“…AM is in the center focus, due to its limitless design manufacturability, various customized material deposition, and ability to automate the manufacturing process, which are few key factors that capitalize over traditional manufacturing methods. AM has achieved immense growth, due to progress in several fields, such as numerical simulations, materials modeling, software development related to AM, customized powder materials preparation for AM, characterizing techniques, and so on [ 1 , 2 , 3 , 4 , 5 ]. Virtual engineering, with the help of numerical modeling, is a powerful tool for the swift progress of AM technology.…”
Section: Introductionmentioning
confidence: 99%
“…A notable improvement in the interfacial properties of matrix and fibers, flexural stiffness, and energy absorption capabilities were observed in that study. Recently, the energy absorption capabilities of lightweight additive manufactured metal/composite hybrid [28,29] lattice structures for shock absorbers applications have been assessed under impact conditions. The study of Miao Zhao et al [30] revealed that the functionally graded sheet lattice structures have 60% higher energy absorption than uniform sheets.…”
Section: Introductionmentioning
confidence: 99%
“…These metallic shock absorbers, even if very effective in reducing the impact peak forces, have been found to significantly increase the vehicle weight. Moreover, their energy absorption capabilities are influenced by different design parameters, as their shape and thickness [ 14 ]. However, variations of the shape and thickness are restricted by the traditional manufacturing techniques, limiting the possibilities in terms of design and material distribution in the components designed to be optimized to the energy absorption tasks.…”
Section: Introductionmentioning
confidence: 99%